The backward child - Burt, Cyril (London : University of London Press, 1961)
This book I am continuing my original purpose of attempting to describe; group by group; the main forms of mental subnormality to be met with among children of school age. In an earlier work on delinquents I dealt with those who are morally subnormal : in the present volume I shall deal with those who are subnormal intellectually $1 (Bwith the backward and the dull.s
Keywords: Children with mental disabilities